58. Cardiovascular responses in patients with symptoms of orthostatic intolerance. Issue 1 (January 2015) - Bongiovanni, L.G.; Barbieri, F.; Rossini, F.; Paluani, F.; Fondreschi, L.; Brigo, F.; Riva, S. Dalla; Monaco, S.
<x xml:space="preserve">Abstract</x> The inability to stand without orthostatic hypotension is the typical disabling clinical symptom of both Postural Tachicardia Syndrome (POTS) and Orthostatic Intolerance (OI). The increase of sinus heart rate of 30 beats/min or greater occurring within 10 min of head-up tilt test or standing, or a heart rate while upright of >120 beats/min. discriminates between the two conditions. To verify if others criteria, beside the difference in heart rate increase, can distinguish the two groups, we analyzed the cardiovascular responses during active standing and head – up tilt test. We analyzed 10 patients with POTS and 10 with OI. Power spectral analysis of blood pressure and heart rate variability, in resting condition and during a period of 30 min of head – up tilt test to 60°, was performed. Both clinical conditions were compared with each other and with a control group using the Student t test. During the head – up tilt both groups of patients showed a marked and comparable increase of LF-RRI and LF/HF ratio in the power spectrum of R–R interval compared to the baseline. This could suggest the hypothesis of OI as a condition preceding POTS.